O ensino de matemática na perspectiva da formação de valores democráticos - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
This research aims to analyze how the learning of mathematics can contribute to the critical / reflexive and democratic formation of the public elementary school students. We seek to classify methodologies of mathematics teaching are indicated for the critical / reflexive and democratic formation of the students of the public basic education system. The main means of working in critical / reflexive formation together with math learning is investigated in literature. With the acquired knowledge, it will be possible to elaborate a didactic sequence that involves financial mathematics, hoping to promote a critical / reflexive mathematics teaching for the students and the understanding of the market system. The target audience for the application of the sequence will be the eighth grade series, at the Santa Terezinha State College, in the city of Petrolina of Goiás. The end product sought at the end of this is a didactic sequence that addresses the formation of values essential to live as full citizens. The nature of this research is qualitative, the researcher as her research field assuming a participant observer role. The data were collected through interviews with teachers and students, and through observations in the daily life of this school. With the development of this work, we note that the appreciation of mathematics by students is practical and immediate, seeking only its momentary application. His reflection that seeks autonomy of thought, when placed at the center, is generally difficult to see, perhaps due to the massification of learning, with the excess of formulas. Thinking about why and why, for these students becomes empty, because it was seen that it is conditioned to the right answer, is often done in their daily lives, not the daily thinking.
Teaching math in the perspective of democratic value formation
Keywords: Cidadania/Democracia; Capitalismo; Formação de valores; Citizenship / Democracy; Capitalism; Formation of values; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS EXATAS E DA TERRA::MATEMATICA; EDUCACAO::ENSINO-APRENDIZAGEM